PENGEMBANGAN JARUM JAM KEMBAR BERCINCIN SEBAGAI ALAT PERAGA MATERI WAKTU PADA SISWA SD KELAS RENDAH - Azizah Thalib (IKIP Siliwangi, 2020)
This research is motivated by the lack of use of educational props, especially in the matter of time. This study aims to develop Jarum Jam Kembar Bercincin props used to assist students in learning mathematics measuring time material that meets valid and practical criteria. This type of research is a research and development (R&D) which consists of several stages, namely preliminary studies, development processes and field trials. The subject of the product trial was grade II students of SDN 1 Kembang, Ampel District, Boyolali Regency. The instruments used were questionnaire and observation sheets. Questionnaire sheet to find out the validity of the media and an observation sheet to find out the practicality of the media. The results showed that Jarum Jam Kembar Bercincin props were suitable for use in learning time material for grade II elementary school students. This is indicated from the validation assessment which obtains very valid criteria with a value of 2.90. Whereas for practicality, it scores 2.52 with practical criteria.